2023
DOI: 10.1142/s2424835523500017
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Outcomes of Open Trigger Release versus Ultrasound-Guided Modified Small Needle-Knife Percutaneous Release for Treatment of Trigger Digits

Abstract: Background: The aim of this randomised prospective study is to compare the outcomes of traditional open trigger digit release versus ultrasound-guided modified small needle-knife (SNK) percutaneous release in the treatment of trigger digits. Methods: Patients with grade 2 and above trigger digits were enrolled into the study and randomly assigned to traditional open surgery (OS) or ultrasound-guided modified SNK percutaneous release group. The patients were followed up for 7, 30 and 180 days after treatment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Regarding side effects and complications, we were unable to conduct a comprehensive analysis due to the absence of reported side effects in the included studies. Lan et al, 26 reported no recurrences (0%) were observed in the open surgery group after 180 days of treatment, while one case (2.86%) recurred in the sonographically assisted needle knife (SNK) group. Notably, there was no significant difference in the recurrence rate between these two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding side effects and complications, we were unable to conduct a comprehensive analysis due to the absence of reported side effects in the included studies. Lan et al, 26 reported no recurrences (0%) were observed in the open surgery group after 180 days of treatment, while one case (2.86%) recurred in the sonographically assisted needle knife (SNK) group. Notably, there was no significant difference in the recurrence rate between these two groups.…”
Section: Discussionmentioning
confidence: 99%